IJTIHAD AS A METHOD OF LEGAL DISCOVERY IN THE ISLAMIC LEGAL SYSTEM - Tamsir, Siti Nashrah Binti; Kafabihi, Mohammad; Zaini, Zaini (TRUNOJOYO LAW REVIEW, 2023)
Although the existence of the Qur'an and Al-Hadith is an authentic source and the basis of law in Islam, this does not close the role of Muslim intellectuals in exploring and establishing the laws needed to solve all problems in the lives of Muslims. Especially on new problems along with the development of science and technology. This research uses the method of literature law by analyzing the legal status of Ijtihad based on literature sources in Islamic legal science. The result obtained in this study is that one of the legal products that can be a source of law in Islam is through the mechanism of Ijtihad as a solution to legal problems in society. Ijtihad is an Islamic appreciation and recognition of the existence of the human mind in solving all problems, one of which is related to Islamic law.